Activity of ETX0462 toward Some Burkholderia spp - Zeiser, Elise T.; Becka, Scott A.; LiPuma, John J.; Papp-Wallace, Krisztina M. (Antimicrobial agents and chemotherapy, 2023)
Burkholderia cepacia complex (Bcc) and Burkholderia gladioli are opportunistic human pathogens that are inherently multidrug resistant, limiting treatment options for infections. Here, a novel diazabicyclooctane, ETX0462, was evaluated for activity against Bcc and B . gladioli . Burkholderia cepacia complex (Bcc) and Burkholderia gladioli are opportunistic human pathogens that are inherently multidrug resistant, limiting treatment options for infections. Here, a novel diazabicyclooctane, ETX0462, was evaluated for activity against Bcc and B . gladioli . Ninety-eight percent of the isolates examined in this study were susceptible. ETX0462 was found to demonstrate in vitro activity superior to that of currently available treatment options (e.g., trimethoprim-sulfamethoxazole and ceftazidime).